COVID-19: Return to youth sports. Preparing sports venues and events for the return of youth sports - Pierce, D.; Stas, J.; Feller, K.; Knox, W. (Sports Innovation Journal, 2020)
COVID-19 has impacted all areas of life, and youth sports is no exception. States and counties are publishing their own unique guidelines for permitting youth sports to return over designated phases, creating a patchwork of guidelines and dates for returning to practice and games. Governing bodies, sports facilities, and event operators are creating modifications and adaptations for participants and spectators to ensure a safe environment. The Sports Innovation Institute at IUPUI, a partnership between Indiana and Purdue universities in Indianapolis, and Grand Park Sports Campus (Westfield, Ind.) collaborated to better understand how COVID-related adaptations are perceived by parents, athletes, coaches, officials, and administrators. The results provide youth sports facilities and event operators with data on how specific adaptions are received by these stakeholders who are looking to return to youth sports in a timely, but safe manner.